EVALUASI PELAYANAN PENDAFTARAN PASIEN PENGGUNA BPJS KESEHATAN TERHADAP WAKTU TUNGGU RAWAT JALAN DI RUMAH SAKIT DR. SUYOTO TAHUN 2023 - Safanny Putri (2024)
Patient waiting time is one of the important factors that can affect patient satisfaction. At dr. Suyoto Hospital, there are many public complaints regarding the length of patient waiting time, especially in the registration unit and outpatient installation. This study aims to evaluate the registration services of BPJS Health users on outpatient waiting times at dr. Suyoto Hospital. This study uses a qualitative descriptive method with the selection of informants using purposive sampling technique. Informants in this study included officers from the registration unit, medical records, and outpatient installations, and also BPJS Health user patients. The results showed that the average outpatient waiting time for patients using BPJS Health at dr. Suyoto Hospital was not in accordance with the standard or ≤ 60 minutes. However, overall registration services had met customer satisfaction. This is due to the long waiting time of patients, especially at the registration counter. The long waiting time of patients is caused by the lack of competence of officers, miscommunication between officers, unavailability of online registration queuing system, merged patient registration counters, as well as tools and technology that often experience problems/disruptions. To overcome this, dr. Suyoto Hospital can do several things, namely by conducting training and development for officers, building coordination and collaboration between officers, providing rewards for the best officers, improving the registration system and flow, and regularly maintain tools and technology to keep them in good condition.